Design of a Real-World Observational Study in Previously Untreated and Minimally Treated Hemophilia A Patients: Protect-NOW - Oldenburg, Johannes; Halimeh, Susan; Hall, Georgina W.; Klamroth, Robert; Vera, Pascual Marco; Jansen, Martina; Mathias, Mary (TH Open, 2023)
Background The efficacy, safety, and immunogenicity of each of Octapharma's factor VIII (FVIII) products, Nuwiq, octanate, and wilate, have been investigated in previously untreated patients (PUPs) with severe hemophilia A in prospective clinical trials. The aim of the Protect-NOW study is to evaluate the effectiveness, safety, and utilization patterns of Nuwiq, octanate, and wilate in PUPs and minimally treated patients (MTPs; <5 exposure days [EDs] to FVIII concentrates or other blood products containing FVIII) with severe hemophilia A in a real-world setting. Real-world data provide valuable information that complement data obtained from interventional clinical trials.Methods Protect-NOW (ClinicalTrials.gov identifier: NCT03695978; ISRCTN identifier: 11492145) is a real-world study in PUPs and MTPs treated with either the human cell line-derived recombinant FVIII Nuwiq (simoctocog alfa) or a plasma-derived FVIII concentrate containing von Willebrand factor (octanate or wilate). It is a prospective and (partly) retrospective, observational, international, noncontrolled, noninterventional study. A total of 140 PUPs and MTPs with severe hemophilia A will be enrolled across around 50 specialized centers worldwide and followed for either 100 EDs or a maximum period of 3 years from ED1. The primary objectives are to assess effectiveness in the prevention and treatment of bleeding episodes and overall safety, including inhibitor development. The secondary objectives are to assess utilization patterns (including dosage and frequency of administration) and the effectiveness in surgical prophylaxis.Conclusions The Protect-NOW study will provide information on the treatment of PUPs and MTPs in routine clinical practice, which will help guide clinical decision making for treating these patients in the future.
Keywords: coagulation factor VIII; hemophilia A; inhibitors; previously untreated patients; real-world study